ANALISIS DATA PANEL FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL KABUPATEN/KOTA DAN PEMERINTAH PROVINSI SELURUH INDONESIA - Totok Susilo Pamuji Nugroho (STIE Atma Bhakti, 2017)
This study aims to determine the effect of Original Income (OI), General Allocation Fund (GAF) and Human Development Index (HDI) to capital expenditures (CE). This study used a sample of financial statements issued BPS center years 2010-2013 and BPK RI at 2014. This study using purposive sampling method, as the sample selection with total sample 165. The method of analysis using linear regression panel data. This study uses a period of five years 2010-2014. The test results H1 testing shows that PAD positive significant effect on capital expenditure. This may imply that the greater the value of PAD, the greater the value of capital expenditures. While the results of testing H2 and H3 shows that DAU and IPM has no effect on capital expenditure. Keywords : capital expenditure, original income, general allocation fund and human development index